Malcolm before X - Parr, Patrick (African American intellectual history, 2024)
"In February 1946, when the 21-year-old Malcolm Little was sentenced to eight to ten years in a maximum-security prison, he was a petty criminal and street hustler in Boston. By the time of his parole in August 1952, he had transformed into a voracious reader, joined the Black Muslims, and was poised to become Malcolm X, one of the most prominent and important intellectuals of the civil rights era. While scholars and commentators have exhaustively detailed, analyzed, and debated Malcolm X's post-prison life, they have not explored these transformative six and a half transformative years in any depth. Utilizing a trove of previously overlooked documents, Patrick Parr immerses readers into the unique cultures of Charlestown State Prison, the Concord Reformatory, and the Norfolk Prison Colony where Malcolm devoured books, composed poetry, boxed, debated, and joined the Nation of Islam. This time in prison changed the course of Malcom's life and set the stage for a decade of antiracist activism that would fundamentally reshape American culture"-- Provided by publisher